Islamic Societies to the Nineteenth Century : a Global History. - Lapidus, Ira M. (Cambridge University Press, 2012)
Based on parts one and two of Ira Lapidus's history, this book traces the transformation of pre-modern Islamic societies and their transfusion globally.